HUBUNGAN STRES DENGAN KEKAMBUHAN GASTRITIS PADA SISWA – SISWI KELAS XII DI SMAN 1 CEPU - Redita, Myrsanila Winny; Kurniawan, Vendi Eko; Hariyono, Rudi (LPPM STIKes Bahrul Ulum Jombang, 2018)
The linkage of stress against recurrence of gastritis when a person in stressful conditions will occur the Nervus Vagus stimulation of the sympathetic dystrophy which causes an increase production of Hydrochloric Acid (HCI) in stomach, it will causing irritation of the gastric mucosa. The purpose of this research is to know the relationship of stress with recurrence of gastritis on the students Grade XII Senior High School 1 Cepu. The design of this research is analytical correlation, the population is the whole of students Grade XII Senior High School 1 Cepu as many as 251 persons. The sampling techniques of this research is purposive sampling (41respondents) with distributed questionnaires to measure the stress level (DASS 42) and recurrence of gastritis quetionnaires. Obtained results that 9 respondents (21.95%) included in a mild stress levels, 9 respondents (21.95%) included in moderate stress levels, 8 respondents (19.51%) included in severe stress levels, and 27 respondents (65.85%) experienced of recurrence of gastritis. The analyze data using statistical test of rank spearman which shows the value of significance of ρ = .002 (ρ ≤ 0,05) means that H1 is accepted, then the conclusion there is the relationship of stress with recurrence of gastritis.Therefore it necessary the positive coping pattern to confront the stressor in order to avoid stress which resulting in recurrence of gastritis